Special education and the law a guide for practitioners - Osborne, Allan G. Jr. 1951-; Russo, Charles J. (Corwin Press, 2021)
"As essential resource for anyone interested in the most up to date and accurate information regarding special education legislation, this book relies on in depth discussion of court cases to help readers to understand statutes and their regulations"--